(untitled) (Homoeopathy for All, 2023)
Understanding Homeopathy: Homeopathy is a form of alternative medicine developed in the late 18th century by Samuel Hahnemann. It is based on the principle of “like cures like,” which means that a substance that causes symptoms in a healthy person can be used in diluted form to treat similar symptoms in an individual suffering from an illness. Homeopathic remedies are prepared through a process of potentization, which involves diluting a substance multiple times and vigorously shaking it. The underlying belief is that this process enhances the healing properties while minimizing any potential toxicity.